Analysis of Fake Authorship from the Perspective of Communication and Hermeneutics - Najafi, Hamed (Frontiers in Law, 2023)
Literary works such as scientific works, after being created, inevitably attract people's attention and somehow, a kind of communication would be stablished between the work and the author. This communication is realized when it is efficient. Communication is effective if the authors of the work are real. Based on all hermeneutic theories, knowing the true authors, has a great impact on the formation of effective communication between the author and his audience through the interpretation and understanding of the text. When an unreal author is included in the work, the understanding of the audience is disturbed and effective communication is not formed. The main issue of this article is what effect does unreal creation have on the understanding of the audience? By using an analytical-descriptive method, we have come to the conclusion that this type of creativity disturbs the audience's understanding and ultimately makes efficient communication difficult.